Ayurvedic Approach to Diabetes Mellitus Associated With Pancreatitis: A Case Study (Prakriti - The International Multidisciplinary Research Journal, 2025)
Diabetes associated with pancreatitis is an increasingly recognized health  concern, primarily arising secondary to pancreatic diseases, with chronic  pancreatitis being the most prevalent cause. In Ayurvedic terms, diabetes  mellitus (Prameha) is associated with Kapha and Pitta vitiation, whereas  pancreatitis is linked to aggravated Pitta disrupting Agni (digestive fire)  and leading to Amaaccumulation. Ayurvedic management integrates di etary modifications, Ayurvedic formulations, and Panchakarma therapies  to restore metabolic balance and enhance pancreatic function. This study  presents the case of a 29-year-old male diagnosed with Diabetes Mellitus  associated with pancreatitis, who sought treatment at Jeena Sikho Lifecare  Limited Hospital, Derabassi, Punjab. He underwent Panchakarma thera pies, including Awagah Swedan, Madhu Tailik Basti, Shiropichu with Brah mi oil, and Nasyam with Anutaila, alongside Ayurvedic formulations. Fol lowing Ayurvedic treatment, the patient experienced significant symptom  relief, improved glycemic control, and better laboratory parameters, includ ing reduced HbA1C levels and improved liver enzyme markers. These find ings highlight the potential of Ayurvedic interventions in managing diabetes  associated with pancreatitis. However, further clinical trials are necessary  to validate these outcomes and establish standardized treatment protocols  for enhanced patient care.
Keywords: Diabetes associated with pancreati tis; Madhumeha; Agni Dushti; Pan chakarma; Basti; Nasyam; Shiropi chu